Pengembangan Majalah Sains Tema Pencemaran Lingkungan Sebagai Bahan Ajar Untuk Menumbuhkan Motivasi Belajar Siswa Kelas VII SMP - Liska Berlin; Muhammad Aminundin Jamal; Lukman Nulhakim (UNIB Press, 2022)
The aim of this study was to develop a science magazine as a teaching material for students on the sub-theme of environmental pollution and to determine the feasibility of this science magazine. The research method used research and development method with the Sugiyono development model. The stages of developing this environmental pollution theme science magazine were: 1) Problem analysis, 2) Data collection, 3) Product design, 4) Product design validation, 5) Product revision, and 6) Product final results. This science magazine was tested by expert validation by several experts from lecturers as well as experts from science subject teachers, and got a validity level from expert I of 100% with very decent criteria, expert II of 65.00% including quite decent criteria, expert III of 95.00% including very feasible criteria, from expert IV 90.00% including very feasible criteria, and expert V by 90.00% with very feasible criteria. Based on the results of the validation test by experts, the average result of the assessment was 88.00% with very feasible criteria.